2006
DOI: 10.1107/s160053680600256x
|View full text |Cite
|
Sign up to set email alerts
|

1,3,5-Tris(4-methylphenyl)benzene

Abstract: Key indicatorsSingle-crystal X-ray study T = 293 K Mean (C-C) = 0.003 Å R factor = 0.054 wR factor = 0.102 Data-to-parameter ratio = 18.9For details of how these key indicators were automatically derived from the article, see

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…13 Inspired by the fact that intrachain charge transfer is beneficial for exciton dissociation and charge generation, a series of CMPs (PCP1x, PCP2x, PCP3x, and PCP4x, Scheme 3b) with alternating building blocks with different electronic properties were synthesized. 153 PCP4e constructed using the strong electron-donating M 8 and the weak electronwithdrawing bipyridyl (bpy) monomer featured a D-A structure and exhibited higher photocatalytic ability with an HER of 9.43 mmol g À1 h À1 . Besides, the D-A structure induced an improvement in electron-hole pair separation, and the higher wettability originating from the hydrogen bonding between the N atoms on bpy and H atoms of water led to a higher concentration of H 2 O molecules around the catalytic sites for reduction.…”
Section: Representative Examplesmentioning
confidence: 99%
See 1 more Smart Citation
“…13 Inspired by the fact that intrachain charge transfer is beneficial for exciton dissociation and charge generation, a series of CMPs (PCP1x, PCP2x, PCP3x, and PCP4x, Scheme 3b) with alternating building blocks with different electronic properties were synthesized. 153 PCP4e constructed using the strong electron-donating M 8 and the weak electronwithdrawing bipyridyl (bpy) monomer featured a D-A structure and exhibited higher photocatalytic ability with an HER of 9.43 mmol g À1 h À1 . Besides, the D-A structure induced an improvement in electron-hole pair separation, and the higher wettability originating from the hydrogen bonding between the N atoms on bpy and H atoms of water led to a higher concentration of H 2 O molecules around the catalytic sites for reduction.…”
Section: Representative Examplesmentioning
confidence: 99%
“…152 The dihedral angle between the benzene and triazine rings in 2,4,6-triphenyl-1,3,5-triazine (TPT) is much smaller than that with benzene as the centre core, which is conducive to the construction of COFs with p-extended structures and tighter interlayer stacking, endowing them with high crystallinity and strong light absorption. 153 B.V. Lotsch et al reported a hydrazone-linked COF (TFPT-COF, Scheme 3g) containing TPT blocks and systematically investigated its performance in photocatalytic hydrogen evolution. 154 As expected, TFPT-COF was highly crystalline and possessed large mesopores of 3.8 nm in diameter together with a high BET surface area of 1603 m À2 g À1 .…”
Section: Representative Examplesmentioning
confidence: 99%
“…The corresponding dihedral angles are 29.30(6) and 37.40(6)°, whereas those in the free compound are 35.15 (7), 39.95(8), and 42.93(6)°. 65 The geometry of the pfp 3 trimer, lying on the twofold rotation axis, follows restrains of the point group 2 (Schoenflies C2), so determined electron density reflects the mean value of two molecules which differ in orientation of the hydrogen bonding loop, so all OH hydrogen atoms are occupied in 1/2 at the two positions. As in the previous example, the complex 2•pfp 3 shows a layered structure, with the layers parallel to (10−1) family of planes, stabilized by the C(sp 3 )−H•••F interactions and the F•••F contacts.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The molecule of 2 in the cocrystal is slightly less twisted than the uncomplexed one. The corresponding dihedral angles are 29.30(6) and 37.40(6)°, whereas those in the free compound are 35.15(7), 39.95(8), and 42.93(6)° . The geometry of the pfp 3 trimer, lying on the twofold rotation axis, follows restrains of the point group 2 (Schoenflies C 2), so determined electron density reflects the mean value of two molecules which differ in orientation of the hydrogen bonding loop, so all OH hydrogen atoms are occupied in 1/2 at the two positions.…”
Section: Resultsmentioning
confidence: 99%